Criteria of Estimation of the Level of Mastering by Students of Technic of Breathing Exercises from Hatha-yoga According to the European Credit Transfer System - Толчєва, Ганна; Tolcheva, Hanna (Східноєвропейський національний університеті імені Лесі Українки, 2015)
На етапі підготовки майбутніх фахівців у вищих навчальних закладах постає проблема збереження їхнього здоров’я. Підвищення характеристик здоров’я студентів пропонується здійснювати за допомогою організації занять із хатха-йоги. Застосування вправ із хатха-йоги потребує розробки критеріїв оцінювання рівня оволодіння студентами техніки за європейською кредитною трансферною системою. Завдання роботи – розробка критеріїв оцінювання рівня оволодіння студентами технікою дихальних вправ із хатха-йоги за шкалою європейської кредитної трансферної системи. Аналізуються засоби практики з хатха-йоги, які можна застосовувати на заняттях зі студентами початкового рівня підготовленості. Надано рекомендації до належного виконання студентами дихальних вправ із хатха-йоги. Обґрунтовано критерії оцінювання рівня оволодіння студентами техніки дихальних вправ із хатха-йоги за національною шкалою та шкалою європейської кредитної трансферної системи. At the stage of preparation of future specialists in higher educational institutions there is a problem of preserving of their health. Increasing of health characteristics of students is offered to be realized by means of organization of hatha-yoga classes. Applying of hathayoga exercises require the development of criteria for evaluating the level of student mastery of the technics of breathing exercises from hatha-yoga according to the scale of the European credit transfer system. The task of the work is to develop criteria for assessing the level of student mastery of the art of breathing exercises of hatha-yoga according to the scale of the European credit transfer system. It was carried out the analysis of the practice facility on hatha-yoga which can be used in the classroom with students of the initial level of preparedness. It was given the recommendations for proper performance by students of breathing exercises from hatha-yoga. It was grounded the criteria of estimation the level of mastery by the students of the breathing exercises technic from hatha-yoga according to the national scale and the scale of the European credit transfer system.
Критерії оцінювання рівня оволодіння студентами технікою дихальних вправ із хатха-йоги за європейською кредитною трансферною системою
Keywords: хатха-йога; дихальні вправи; шкала; критерії; оцінювання; студент; Європа; hatha-yoga; breathing exercises; scale; criteria; estimation; student; Europe